TLR2 Signaling is Required for the Innate, but Not Adaptive Response to LVS clpB - Roberts, Lydia M.; Ledvina, Hannah E.; Sempowski, Gregory D.; Frelinger, Jeffrey A. (Frontiers in Immunology, 2014)
Toll-like receptor 2 (TLR2) is the best characterized pattern-recognition receptor for the highly pathogenic intracellular bacterium, Francisella tularensis. We previously identified a mutant in the live vaccine strain (LVS) of Francisella, LVS clpB, which is attenuated, but induces a protective immune response. We sought to determine whether TLR2 signaling was required during the immune response to LVS clpB. TLR2 KO mice previously infected with LVS clpB are completely protected during a lethal challenge with LVS. Furthermore, the kinetics and magnitude of the primary T cell response in B6 and TLR2 KO mice are similar indicating that TLR2 signaling is dispensable for the adaptive immune response to LVS clpB. TLR2 signaling was important, however, for the innate immune response to LVS clpB. We identified three classes of cytokines/chemokines that differ in their dependence on TLR2 signaling for production on day three post-inoculation in the broncheoalverolar lavage fluid. IL-1α, IL-1β, IL-2, IL-17, MIP-1α, and TNF-α production depended on TLR2 signaling while GM-CSF, IFN-γ, and VEGF production were completely independent of TLR2 signaling. IL-6, IL-12, IP-10, KC, and MIG production were partially dependent on TLR2 signaling. Together our data indicate that the innate immune response to LVS clpB requires TLR2 signaling for the maximal innate response whereas TLR2 is not required for the adaptive immune response.